Computer system for diagnostic and treatment of unilateral neglect syndrome - Strzecha, Krzysztof; Bukalska-Strzecha, Agata; Kurzdym, Krzysztof; Sankowski, Dominik (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2025)
Unilateral Spatial Neglect (USN) is a neuropsychological disorder commonly resulting from right hemisphere brain damage, leading to impaired awareness of stimuli on the left side of space. It significantly affects patient autonomy and rehabilitation outcomes. Traditional therapies such as Visual Scanning Training (VST) and Prism Adaptation (PA) lack standardization and objective diagnostic tools. This paper presents a computer-based system designed to support both diagnosis and therapy of USN. The system uses a 5-meter LED strip to deliver spatially distributed visual stimuli and records patient responses via a physical button. Reaction times and detection data are stored in a local database, enabling objective assessment and personalized therapy planning. The system architecture is modular, based on Clean Architecture principles, and implemented in C++20 on a Raspberry Pi 5 microcomputer. The graphical interface is built using GTKmm 4.0. Therapy sessions follow VST methodology. They include tracking moving stimuli, using visual anchors, and increasing stimulus density. Preliminary trials confirm the system’s ability to differentiate neglect symptoms and support individualized therapy. Its portability, modularity, and integration of diagnostic and therapeutic functions make it a promising tool for clinical neurorehabilitation. Further validation and development are planned to support broader clinical adoption.